Status of the SIRGAS reference frame: recent developments and new challenges - Alves Costa, Sonia M. (2023)
In accordance with recent developments of the International Association of Geodesy (IAG) and the policies promoted by the Subcommittee on Geodesy of the United Nations Committee of Experts on Global Geospatial Information Management (UN-GGIM), a main goal of the Geodetic Reference System for the Americas (SIRGAS) is the procurement of an integrated regional reference frame. This frame should support the precise determination of geocentric coordinates and also provide a unified physical reference frame for gravimetry, physical heights, and a geoid. The geometric reference frame is determined by a network of about 500 continuously operating GNSS stations, which are routinely processed by ten analysis centers. The GNSS solutions from the analysis centers are used to generate weekly station positions aligned to the International Terrestrial Reference Frame (ITRF) and multi-year (cumulative) reference frame solutions. This processing is also the basis for the generation of precise tropospheric zenith path delays with an hourly sampling rate over the Americas. The reference frame for the determination of physical heights is a regional densification of the International Height Reference Frame (IHRF). Current efforts focus on the estimation and evaluation of potential values obtained from high resolution gravity field modelling, an activity tightly coupled with geoid determination. The gravity reference frame aims to be a regional densification of the International Terrestrial Gravity Reference Frame (ITGRF). Thus, SIRGAS activities are focused on evaluating the quality of existing absolute gravity stations and to identify regional gaps where additional absolute gravity stations are needed. Another main goal of SIRGAS is to promote the use of its geodetic reference frame at the national level and to support capacity building activities in the region. This paper summarizes key milestones in the establishment and maintenance of the SIRGAS reference frame and discusses current efforts and future challenges.